Exploring the black box: technology, economics and history, Nathan Rosenberg, Nueva York, Cambridge University Press, 1994, 274 páginas. - Lemarchand, Guillermo (1994)
Fil: Lemarchand, Guillermo A. Universidad de Buenos Aires. Centro de Estudios Avanzados; Argentina.